(untitled) (Colombia Medica, 1989)
Newborn hematological problems, mainly leukopenia and thrombocytopenia, have been associated with toxemia of pregnancy. From toxemic mothers, most of them with severe disease, 81 newborns were followed looking for hematological alterations. As controls, 21 healthy newborns were taken. The study was done at Hospital Universitario del Valle in Cali, Colombia, from September to November 1987. More perinatal asphyxia was found in toxemic mothers’ children who had higher hematocrit and lower neutrophils without reaching levels of neutropenia. In the most severe forms of toxemia, the babies had alterations in the platelet count, either thrombocytopenia or thrombocytosis, which is the last finding (thrombocytosis) not reported previously. Finally, the medications administered to the mothers to control the disease did not alter the platelet count in the babies. In the newborns, even with the most severe forms of toxemia, no leucopenia or thrombocytopenia was found.